Ethical governance of clinical research on the brain–computer interface for mental disorders: a modified Delphi study - Qing Zhang; Zhen Wang; Jing Chen; Chen Zhang; Tianhong Zhang; Yifeng Xu; Haiqing Ji; Xingchao Wang; Pinan Liu (General Psychiatry, 2025)
Background Clinical brain–computer interface (BCI) for mental disorders is an emerging interdisciplinary research field, posing new ethical concerns and challenges, yet lacking practical ethical governance guidelines for stakeholders and the entire community.Aims This study aims to establish a multidisciplinary consensus of principles for ethical governance of clinical BCI research for mental disorders and offer practical ethical guidance to stakeholders involved.Methods A systematic literature review, symposium and roundtable discussions, and a pre-Delphi (round 0) survey were conducted to form the questionnaire for the three-round modified Delphi study. Two rounds of surveys, followed by a third round of independent interviews of 25 experts from BCI-related research domains, were involved. We conducted quantitative analysis of responses and agreements among experts to reveal the consensus and differences regarding the ethical governance of mental BCI research from a multidisciplinary perspective.Results The Delphi panel emphasised important concerns of ethical review practices and ethical principles within the BCI context, identified qualified and highly influential institutions and personnel in conducting and advancing clinical BCI research, and recognised prioritised aspects in the risk–benefit evaluation. Experts expressed diverse opinions on specific ethical concerns, including concerns about invasive technology, its impact on humanity and potential social consequences. Agreement was reached that the practices of ethical governance of clinical BCI for mental disorders should focus on patient voluntariness, autonomy, long-term effects and related assessments of BCI interventions, as well as privacy protection, transparent reporting and ensuring that the research is conducted in qualified institutions with strong data security.Conclusions Ethical governance of clinical research on BCI for mental disorders should include interdisciplinary experts to balance various needs and incorporate the expertise of different stakeholders to avoid serious ethical issues. It requires scientifically grounded approaches, continuous monitoring and interdisciplinary collaboration to ensure evidence-based policies, comprehensive risk assessments and transparency, thereby promoting responsible innovations and protecting patient rights and well-being.